Can Transabdominal Scan Predict a Short Cervix by Transvaginal Scan?. (9th April 2017) - Nambiar, Jayaraman Mavila; Pai, Muralidhar Vaman; Reddy, Arevidya; Kumar, Pratap
Abstract : Background . To determine whether transabdominal screening can be used to screen women with short cervix on transvaginal scan. Methods . The study was done between 18 and 20 weeks of gestation. Transabdominal scan was done and cervical length was measured. Transvaginal scan was also done and cervical length was measured. An attempt was made to find out whether transabdominal scan be used to predict a cervical length of 25 mm by transvaginal scan. Results . In our study the cut-off for transabdominal scan for detecting a short cervix of 25 mm by transvaginal scan was 29 mm. A transabdominal cervical length of 29 mm could predict a short cervix of 25 mm by transvaginal scan by 100% sensitivity and 92.4% sensitivity. Conclusion . A cut-off of 29 mm by transabdominal scan is very accurate in predicting a short cervix of 25 mm by transvaginal scan.